VALIDITY AND RELIABILITY OF REBT MODULE CREATIVE GUIDANCE ON IRRATIONAL THINKING, AGGRESSIVE BEHAVIOR, AND SELF-ESTEEM - Ibrahim Abd Ghani; Norsayyadatina Che Rozubi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Rational Emotive Behavioural Therapy (REBT) Module - Creative Guidance is designed to prevent irrational thoughts, lower aggressive behavior, and increase self-esteem. This module contains seven sub-modules based on behavioral approaches based on the theory of Rational Emotive Behavior Therapy (REBT) by Albert Ellis (1955) and integrated with creative Guidance. It combines elements of Music, technology, and play. To measure the validity of the content, the certification method by five experts was used while 40 primary school students aged 11 years were selected to follow the guidance program using this module. It is run for two weeks in a row. The findings of the study show that the REBT-Creative Guidance Module has a content validity index value of 80%., The cost of Cronbach’s Alpha coefficient of Creative REBT-Guidance Module is high at .978. Reliability with an amount.930 In conclusion, new contributions to guidance and counseling teachers in Malaysia. It is also suitable for use in a local context focused on primary school students. Counselors can also use this module, Teachers or facilitators as one of the alternative interventions for primary school students throughout Malaysia, especially on the Development and Development of Student Personality, Improving Student Discipline, Improving Student Careers and Psychosocial and Mental Well-Being.